Identifying regions in prefrontal cortex related to working memory improvement: A novel meta-analytic method using electric field modeling. (November 2021) - Wischnewski, Miles; Mantell, Kathleen E.; Opitz, Alexander
Highlights: We summarize the effect of 87 tDCS studies on working memory performance. We introduce a new meta-analytic method correlating tDCS electric fields and performance. tDCS-induced electric fields in lower DLPFC correlate significantly with improved working memory. The lower DLPFC was not maximally targeted by most tDCS montages and we provide an optimized montage. Abstract: Altering cortical activity using transcranial direct current stimulation (tDCS) has been shown to improve working memory (WM) performance. Due to large inter-experimental variability in the tDCS montage configuration and strength of induced electric fields, results have been mixed. Here, we present a novel meta-analytic method relating behavioral effect sizes to electric field strength to identify brain regions underlying largest tDCS-induced WM improvement. Simulations on 69 studies targeting left prefrontal cortex showed that tDCS electric field strength in lower dorsolateral prefrontal cortex (Brodmann area 45/47) relates most strongly to improved WM performance. This region explained 7.8 % of variance, equaling a medium effect. A similar region was identified when correlating WM performance and electric field strength of right prefrontal tDCS studies (n = 18). Maximum electric field strength of five previously used tDCS configurations were outside of this location. We thus propose a new tDCS montage which maximizes the tDCS electric field strength in that brain region. Our findings can benefit future tDCS studies that aim to affect WM function.